Income taxes, death taxes, and optimal consumption-leisure-savings-choice - Ulrich van Suntum (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2008)
An optimal taxation approach is employed to compare a proportional income tax with a death tax within a simple lifetime-cycle-model. The impact of both taxes is discussed concerning consumption, leisure, savings, and inheritance. It is shown that the income tax generally leaves the tax payer with a higher residual utility than does the death tax, if the same present value of tax receipts is supposed. Moreover, the death tax is much more limited concerning the maximum possible tax receipts than is the income tax. It is argued that there is a double dividend of heritages because of positive consumption externalities, which should not be destroyed by undue taxation. Taking that into account within a steady-state OLG- model, the death tax turns out to be the least efficient tax at all.
Keywords: 330